2010
DOI: 10.1590/s1982-56762010000100001
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the rice root nematode Hirschmanniella oryzae on monsoon rice in Myanmar

Abstract: During May-October 2007, soil and root samples from 539 fields were collected from 11 monsoon rice varieties in 12 regions in Myanmar. All regions surveyed and 90% of fields sampled were infested with the rice root nematode Hirschmanniella oryzae. The average H. oryzae population was 10/100 mL soil and 419/20 g roots respectively. In 6.9% of the fields sampled 50 H. oryzae/g root were found. The average root population densities were the highest (640/20 g roots) in Taungpyan variety and the lowest (155/20 g ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 4 publications
3
12
0
2
Order By: Relevance
“…In our study, H. oryzae root population density declined sharply between the heading stage and harvesting, while the soil population reached its highest peak of the rice-growing season. This observation supports previous reports that H. oryzae exit the decaying roots after flowering, which occur 2-3 days after the heading stage (Merny, 1972;Prot, 1994), resulting in low root population densities at harvest (Arayarungsarit & Junbuthong, 1988;Hendro et ctl, 1992;Youssef & El-Hamawi, 1996;Youssef, 1999;Islam et al, 2004;Maung, 2011). In the soil, H. oryzae may survive for several months waiting to infect newly formed rice roots (Walawala & Davide, 1984).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, H. oryzae root population density declined sharply between the heading stage and harvesting, while the soil population reached its highest peak of the rice-growing season. This observation supports previous reports that H. oryzae exit the decaying roots after flowering, which occur 2-3 days after the heading stage (Merny, 1972;Prot, 1994), resulting in low root population densities at harvest (Arayarungsarit & Junbuthong, 1988;Hendro et ctl, 1992;Youssef & El-Hamawi, 1996;Youssef, 1999;Islam et al, 2004;Maung, 2011). In the soil, H. oryzae may survive for several months waiting to infect newly formed rice roots (Walawala & Davide, 1984).…”
Section: Discussionsupporting
confidence: 89%
“…Our results are in agreement with previous observations by Kuwahara & Iyatomi (1970), cited by Fortuner& Merny (1979), who reported that, in Japan, the highest population density of H. oryzae in rice roots occurs at the heading stage irrespective of the date of planting. Maung (2011) observed the highest root population densities of H. oryzae at the milky grain stage which follows the heading stage. In our study, H. oryzae root population density declined sharply between the heading stage and harvesting, while the soil population reached its highest peak of the rice-growing season.…”
Section: Discussionmentioning
confidence: 85%
“…Several species are a serious economic threat to lowland rice fields in South and Southeast Asia (Bridge et al, 1990;Prot et al, 1994;Karssen, 2009;Maung et al, 2010;Win et al, 2013). For example, when H. oryzae (van Breda de Haan, 1902) Luc & Goodey, 1964 was present in the field before rice seedlings were transplanted, tiller growth was reduced by up to 50-60% and yield production decreased by at least 25% (Ou, 1985;Jairajpuri & Baqri, 1991).…”
mentioning
confidence: 99%
“…These results confirm those of several research studies on rice parasitic nematode communities. Indeed, several studies have noted the predominance of nematodes belonging to the genus Hirschmanniella known as the most frequent and most damaging to rice in lowland and irrigated ecologies (Coyne et al, 2000;Ravichandra et al, 2003;Bridge et al, 2005;Maung et al, 2010;Udo et al, 2011;Thio et al, 2017).…”
Section: Discussionmentioning
confidence: 99%